(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Flame stability is one of the main challenges facing the different combustion applications. A lot of undesirable phenomena such as blow-off and flashback may occur according to the instability of the flame causing damage to the overall combustion system. Therefore, it is necessary to develop methods which help improve the combustion process and obtain wider flame stable regions. Among these methods, swirling flows and bluff-bodies are the most commonly used in flame stabilization. These may create central recirculation zones (CRZ’s) that, in turn, recirculate the heat and active chemical species to the root of flame, improving the reactants mixing and as a result, flame stability. Hence, the current article presents an overview of flame stability mechanisms and the operation map using swirling flows and bluff-bodies. The effect of the swirl number (S) and burner’s geometry, as well as the influence of the bluff-body shape, size and position on the flame stabilization mechanisms are discussed.